PENGARUH FIBONACCI RETRACEMENT TERHADAP RETURN SAHAM BANK DIGITAL - Mediaty , Mediaty; Habbe, Abdul Hamid; Nur, Hamzah Fansyuri; Kurniawan, Awi; Uswatun Hasanah; Putriyanti, Indah (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: The purpose of this research is to find out whether the Fibonacci Retracement influences stock returns using Fibonacci ratios in banking sector companiesMethods: This study employs a quantitative methodology, utilizing a sample of digital bank companies listed on the Kompas 100 index for the 2022 period.Results: The results of this study indicate that the effect of the Fibonacci retracement on stock returns is insignificant, with an independent variable value of 1 > 0.01 and a VIF value of 1 < 10. So it can be concluded that the Fibonacci retracement has no comfort with stock returns. Keywords: (Fibonacci Retracement, Support, Resistance, Return).